Opera Scenes for Class and Stage - Wallace, Mary Elaine (Book collections on Project MUSE., 2013)
"This reference work provides access to more than seven hundred excerpts from one hundred arias by voice categories and furnishes authoritative information on a variety of matters of interest to directors, teachers, and singers"--